Pengaruh Tingkat Pendapatan, Kesadaran Wajib Pajak, Penegasan Sanksi Pajak, Dan Layanan E-Samsat Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor (Studi Kasus Pada Wajib Pajak Kendaraan Bermotor Di Kantor Samsat Karawang) - Reka Rosita; Yanti Yanti; Awaliawati Rachpriliani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to examine the effect of income level, taxpayer awareness, tax sanction enforcement, and e-samsat services on motor vehicle taxpayer compliance (a case study on motorized vehicle taxpayers at the Karawang Samsat Office). The data collected is in the form of primary data using questionnaires with a quantitative approach. The population in the study were motor vehicle taxpayers registered at the Karawang Samsat office with a sample of 100 people using the Accidental Sampling technique. The data analysis method uses the Partial Least Squares (PLS) analysis technique with the SmartPLS version 4.0 application. The results of the study show that income levels have a positive and significant effect on motor vehicle taxpayer compliance, taxpayer awareness has a positive and significant effect on motor vehicle tax compliance, affirmation of tax sanctions has a negative and insignificant effect on motor vehicle taxpayer compliance, e-service -Samsat has a positive and significant influence on motor vehicle taxpayer compliance. Keywords: Income Level, Taxpayer Awareness, Tax Sanction Affirmation, E-Samsat Service, Motor Vehicle Taxpayer Compliance